PENGEMBANGAN MEDIA PEMBELAJARAN LAPBOOK BERBASIS KEARIFAN LOKAL PADA MATA PELAJARAN IPAS SISWA KELAS V SDN 2 SURODADI - Galuh Eky Arsanti; Eka Lokaria; Andriana Sofiarini (Linggau Journal Science Education (LJSE), 2026)
This study aims to produce Lapbook media in the subject of Natural Sciences. Testing the validity, practicality and effectiveness of Lapbook media based on local wisdom in the Natural Sciences lesson of SDN 2 Surodadi students. This type of research is Research and Development with a 4D development model. The subjects of this study were fifth grade students of SDN 2 Surodadi. Data collection techniques used interviews, questionnaires, tests, and documentation. Based on the results of the validity of the Lapbook media by the assessment of linguists, material experts and media experts, it shows that the Lapbook media meets the valid criteria with an average score of 0.96. Meanwhile, from the practicality assessment sheet of teachers and students, it was obtained that the Lapbook media met the very practical criteria with an average score of 94.15. In the large group test, an N-Gain of 1.06 was obtained with a high classification. Based on the results of the study, it can be concluded that the Lapbook media based on local wisdom is proven to be valid, practical, and effective for the Natural Sciences lesson of SDN 2 Surodadi students.